2020
DOI: 10.1111/fme.12467
|View full text |Cite
|
Sign up to set email alerts
|

Risk analysis of non‐native three‐spot cichlid, Amphilophus trimaculatus, in the River Cauvery (India)

Abstract: The three‐spot cichlid Amphilophus trimaculatus (Günther) is an ornamental fish known to be invasive but has not been assessed for India. The present study confirmed this non‐native species’ identity using conventional and molecular methods, as well as its occurrence in the River Cauvery, the first for this species in a lotic environment outside its native range. Gut content analysis indicated a diet of predominantly insects. The river's water quality and habitat were conducive for the species’ growth and repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Nasution et al (2022) reported A. trimaculatum population is relatively abundant in the littoral zone of Lake Mahalona, Sulawesi, consisted of up to 21.34% from the total population structure despite being an alien species. Reports outside Indonesia included India's Lake Chenai (Daniel et al 2020) and River Cauvery (Kumar et al 2020) where the fish exhibited predatory behavior and may deter predation by having spiny dorsal fins. The potential for flowerhorn fish to become an invasive species should be considered in the aquarium trade; as a result, fish distributors and owners should check the regulations and avoid releasing the fish into the local environments.…”
Section: Discussionmentioning
confidence: 99%
“…Nasution et al (2022) reported A. trimaculatum population is relatively abundant in the littoral zone of Lake Mahalona, Sulawesi, consisted of up to 21.34% from the total population structure despite being an alien species. Reports outside Indonesia included India's Lake Chenai (Daniel et al 2020) and River Cauvery (Kumar et al 2020) where the fish exhibited predatory behavior and may deter predation by having spiny dorsal fins. The potential for flowerhorn fish to become an invasive species should be considered in the aquarium trade; as a result, fish distributors and owners should check the regulations and avoid releasing the fish into the local environments.…”
Section: Discussionmentioning
confidence: 99%
“…importation/ commercial exploitation/evaluation of existing impacts for a specific risk assessment area (e.g. Castellanos-Galindo et al 2018;Suresh et al 2019;Baduy et al 2020;Zięba et al 2020;Haubrock et al 2021;Kumar et al 2021;Yoğurtçuoğlu et al 2021).…”
Section: Discussionmentioning
confidence: 99%